Don't neglect the soul - Noor, Noraini M. (One Page, 2010)
Malaysia is a mult-ethnic society with Malays, Chinese, Indians and others. Each group has its own separate language, culture, and religion based on animism, Hinduism, Buddhism and Islam. Professor Noraini M. Noor works at the International Islamic University of Malaysia in Kuala Lumpur. Most of her Malay students find it difficult to grasp the concept of 'happiness'. She looks for an answer in the culture and religion of the Malays.